2018
DOI: 10.1080/21645515.2018.1520583
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus vaccine efficacy: current status and areas for improvement

Abstract: The difference noted in Rotavirus vaccine efficiency between high and low income countries correlates with the lack of universal access to clean water and higher standards of hygiene. Overcoming these obstacles will require great investment and also time, therefore more effective vaccines should be developed to meet the needs of those who would benefit the most from them. Increasing our current knowledge of mucosal immunity, response to Rotavirus infection and its modulation by circadian rhythms could point at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 130 publications
(190 reference statements)
0
45
0
2
Order By: Relevance
“…Lower efficacy (49.7–64.5%) in clinical trials and effectiveness (18–69%) of the RVVs have been observed in LMICs from Africa, Latin America and Asia compared to the middle and high income countries [40] , [5] . The lower immune responses to the RVVs may be due to lower replication of the RVV viruses in the intestine of infants in LMICs, which is reflected in lower fecal shedding [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Lower efficacy (49.7–64.5%) in clinical trials and effectiveness (18–69%) of the RVVs have been observed in LMICs from Africa, Latin America and Asia compared to the middle and high income countries [40] , [5] . The lower immune responses to the RVVs may be due to lower replication of the RVV viruses in the intestine of infants in LMICs, which is reflected in lower fecal shedding [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus is the leading cause of severe gastroenteritis in children less than 5 years of age (Crawford et al 2017) and also a common cause of diarrhea in young animals (Doro et al 2015). Although effective live-attenuated vaccines are available for human rotavirus infection (Carvalho and Gill 2019), rotavirus still remains the most important cause of gastroenteritis in infants and children worldwide. Kim and Chang demonstrated that CDCA and DCA significantly reduced rotavirus replication in cell culture in a dose-dependent manner with activation of FXR/small heterodimer partner signaling pathway.…”
Section: Roles Of Bas In the Replication Of Enteric Rotavirusmentioning
confidence: 99%
“…The vaccination of mice with DCs loaded with antigen leads to the expansion of specific CD8 + T cells and a better efficiency for a bacterial challenge if the vaccination is done in the middle of the day as compared with other time points. This response is abrogated when the Bmal1 gene is invalidated in DCs ( 142 ) Even if these results are promising, confirmation in other types of vaccination remains required.…”
Section: Circadian Rhythms and Management Of Infected Patientsmentioning
confidence: 99%